PLATFORM E-WARUNG KOBER UNTUK MENDUKUNG MODEL KETAHANAN PANGAN MASYARAKAT DAMPAK PANDEMI COVID 19 UNTUK MASYARAKAT KAB KEBUMEN - Kurniadi, Dedy; Sugiyono, Andre; Ghufron, Ghufron (Jurnal Ilmiah Sultan Agung, 2025)
Abstract: Electronic Program stalls Joint Business Group Family Hope Program (E-Warung KUBE- PKH) is one of the programs to overcome poverty. In view of this program from the Ministry of Social Affairs, the delegation of authority in implementing the empowerment of E-Warung KUBE-PKH program located in Kab.Kebumen City was handed over to the Social Service of Kab.Kebumen City. The research method used is qualitative research with data collection steps through interview, observation and documentation. The results of the study found that the role of Social Service in the implementation of the empowerment of the poor through the E-Warung KUBE-PKH program in Kab.Kebumen is good enough that the Social Service has provided socialization and facilitate the activities of electronic program stalls, providing mentoring and training to the public electronic managers stalls , the community is able to be independent in the management of assistance and use of ATM card and Electronic Data Capture (EDC), problem solving is done based on agreement and understanding of the need of electronic member of stall. But there are still obstacles that is, the delay of assistance and the difference in behavior patterns of electronic managers stalls that have an impact on the inactivity of some electronic stalls in the city of Kab.Kebumen . Keywords: Role of Social Service, Empowerment, Electronic Program stalls